Use of silver nanoparticles for controlling Burkholderia glumae in rice: Characterization and field results - Gonzáles-Gonzáles, Jeyson Adrian; Ortiz-Rojas, Luz Yineth; Chaves-Bedoya, Giovanni (Revista de Ciencias Agrícolas, 2025)
Rice, Oryza sativa L., serves as a staple food for a substantial portion of the global population, making its protection against pathogens like Burkholderia glumae critically important. While recent studies have explored various nanotechnological approaches for phytopathogen control, the specific field application of silver nanoparticles against B. glumae remains poorly documented. This study evaluated the field efficacy of silver nanoparticles (AgNPs) as a treatment against B. glumae, comparing them with traditional methods such as Starner WP (a synthetic fungicide) application. AgNPs were synthesized electrochemically and characterized by UV/VIS spectrophotometry. Burkholderiaglumae detection was performed using Polymerase Chain Reaction (PCR). Employing a randomized block design, various growth parameters of rice seedlings were analyzed during five weeks post-treatment. Application of AgNPs improved yield parameters by reducing the incidence of grains affected by B. glumae by 45%, increasing the total grain number by 20%, and raising grain weight by 15%. In contrast, root volume decreased by about 10%, a finding consistent with prior greenhouse research. Treated seedlings exhibited more intense green foliage, suggesting improved plant health. These results were corroborated by morphological variations, indicating differential impact on growth and disease resistance. This study provides valuable insights into nanotechnology applications for sustainable agriculture and emphasizes the need for a multifaceted approach to disease management in rice. AgNPs represent a promising sustainable alternative to conventional bactericides.